Ιουλία Βοκοτοπούλου, Ιωακείμ Α. Παπάγγελος, Ευαγγελία Καμπούρη, Λόης Λαμπριανίδης, Λευτέρης Παπαγιαννάκης, Θύμιος Παπαγιάννης, Γερακίνα Μυλωνά; Χαλκιδική, Ιερό Κοινόβιο Ευαγγελισμού της Θεοτόκου-Ορμύλια - Στρατή, Αγγελική (Μακεδονικά, 2004)
No abstract